Assessment of proliferative activity in leukaemic bone marrow using the monoclonal antibody Ki-67. - White, D M (1994)
AIMS--To investigate proliferative activity in leukaemic and lymphomatous bone marrow infiltrates and to assess the feasibility of transport of specimens among institutions. METHODS--Proliferative activity in bone marrow trephine cryosections from 99 patients with non-Hodgkin's lymphoma (NHL), 23 patients with acute myeloid leukaemia (AML), 11 with acute lymphoblastic leukaemia (ALL), and two with acute undifferentiated leukaemia (AUL) was investigated. Infiltration was seen in 52 out of 99 cases of NHL on bone marrow cryosections. A score was devised to assess pathological infiltrates in bone marrow trephine cryosections using the monoclonal antibody Ki-67. This method of scoring gave a measure of non-erythroid proliferative activity. RESULTS--Mean Ki-67 positivity in bone marrow infiltrates in 31 low grade B cell lymphomas (Kiel classification) was 0.3% before and 4.7% after treatment, 16.4% in seven high grade B cell lymphomas, and 17.8% in 12 peripheral T cell lymphomas. In 48 cases of NHL, bone marrow cryosections had not been infiltrated, and in all but one case the percentage of Ki-67 positive cells in normal marrow was less than 3%; the remaining case showed coexistent myelodysplasia and 8% bone marrow Ki-67 positivity. In eight cases of common ALL at diagnosis, the mean Ki-67 positivity in marrow cryosections was 24.9%, significantly higher than the 2.4% Ki-67 positivity seen in AML (p < 0.05). One of the two cases of common ALL with less than 1% Ki-67 positivity was refractory to treatment. CONCLUSIONS--Proliferative activity of erythroid elements in the bone marrow varies greatly. Immunostaining of bone marrow cryosections using Ki-67 permits accurate assessment of non-erythroid proliferative activity in lymphomas and leukaemia. High grade B cell lymphomas and peripheral T cell lymphomas invading the marrow have very similar mean proliferative activities. Such levels of proliferation are of the same order as those seen in common ALL, but much higher than those seen in AML.